2021
DOI: 10.1186/s40634-020-00320-z
|View full text |Cite
|
Sign up to set email alerts
|

Promising improvement of chronic lateral elbow tendinopathy by using adipose derived mesenchymal stromal cells: a pilot study

Abstract: Purpose Study the effect of Adipose derived stromal cells (ASCs) injection as therapeutic procedure on the common extensor tendinopathy. Methods Eighteen Tennis players with chronic, recalcitrant LET (who have previously been unsuccessfully treated with nonoperative treatments) underwent clinical evaluation and magnetic resonance imaging (MRI) before intervention. Stromal vascular fraction cells (SVF) were expanded by in vitro culture and ASCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 42 publications
2
40
0
3
Order By: Relevance
“…Clarke et al [9] using ultrasound-guided injection of expanded autologous skin-derived tendon-like cells concluded that they can be safely used to treat patellar tendinopathy with, in the short term, faster response of treatment and significantly greater improvement in pain and function than injection of plasma alone. The use of ASCs to treat lateral elbow tendinopathy with promising results has also been reported by our group [19]. It has been previously shown that the responsiveness of the VISA-P scale for patellar tendinopathy in athletes who showed an absolute change greater than 13 points in the VISA-P score (or 15.4-27% of relative change) achieved a 98% probability of a minimal important change (MICD) in their status.…”
Section: Discussionsupporting
confidence: 63%
“…Clarke et al [9] using ultrasound-guided injection of expanded autologous skin-derived tendon-like cells concluded that they can be safely used to treat patellar tendinopathy with, in the short term, faster response of treatment and significantly greater improvement in pain and function than injection of plasma alone. The use of ASCs to treat lateral elbow tendinopathy with promising results has also been reported by our group [19]. It has been previously shown that the responsiveness of the VISA-P scale for patellar tendinopathy in athletes who showed an absolute change greater than 13 points in the VISA-P score (or 15.4-27% of relative change) achieved a 98% probability of a minimal important change (MICD) in their status.…”
Section: Discussionsupporting
confidence: 63%
“…Another study where 18 tennis players were treated with approximately 8 × 10 6 autologous ADSCs for recalcitrant lateral elbow tendinopathy indicated that ADSC therapy significantly improved clinical parameters readily at one month following injection and structural repair of the origin of common extensor tendon at six months after injection [ 142 ], without any joint effusion or skin hypersensitivity reactions that had been observed in the previous similar study where allogeneic ADSCs were used [ 141 ].…”
Section: Type Of Msds Targetedmentioning
confidence: 99%
“…Among the seven studies included, three were performed in Korea [55][56][57], one in Italy [58], two in Argentina [59,60] and one in Australia [61]. In particular, two were classified as prospective longitudinal-case serious exploratory studies [59,60], one as cohort study [55], one as first-in human trial [56], one as randomized controlled clinical trial [58], one as open-label study [57] and one as case report [61].…”
Section: Study Design and Methodsmentioning
confidence: 99%